Occurrence of Gnathostoma spinigerum in a leopard cat from Wayanad Wildlife Sanctuary, Kerala - Lenka, Dibya Ranjan (J Parasit Dis, 2014)
The post-mortem examination of a leopard cat from Wayanad Wildlife Sanctuary, Kerala, died in a road accident, revealed presence of gastric tumours containing worms which were identified as Gnathostoma spinigerum based on morphological characteristics.